Descriptive Review on Liposomal Drug Delivery System: Review Article (Journal of Pharma Insights and Research, 2024)
Liposomal drug delivery systems have transformed pharmaceutical science, offering a versatile platform for enhancing drug efficacy and reducing toxicity. These microscopic vesicles, composed of lipid bilayers, can encapsulate both hydrophilic and lipophilic drugs, significantly improving their pharmacokinetic profiles. Recent advancements include the development of stimuli-responsive and targeted liposomes, expanding their therapeutic potential across various medical fields. The unique pharmacokinetics and biodistribution of liposomal formulations contribute to their improved drug delivery capabilities. However, challenges persist in liposome stability, drug loading efficiency, and large-scale production. Innovative solutions are being developed to address these issues, including novel lipid compositions and manufacturing techniques. Liposomes have shown remarkable potential in cancer therapy, gene delivery, vaccine development, and diagnostic imaging. The integration of liposomes with nanotechnology has opened new avenues for targeted drug delivery and theranostic applications. Emerging trends also highlight their role in personalized medicine. Despite challenges, liposomal drug delivery systems continue to evolve, promising significant advancements in therapeutic interventions and paving the way for more effective and tailored treatment strategies in modern medicine